Zinc cadmium oxide thin film transistors fabricated at room temperature - Lee, Deuk-Hee; Kim, Sangsig; Lee, Sang Yeol (ELSEVIER SCIENCE SA, 2011)
Zinc cadmium oxide (ZnCdO) transparent thin film transistors (TFTs) have been fabricated with a back-gate structure using highly p-type Si (001) substrate. For the active channel, 30 nm, 50 nm, and 100 nm thick ZnCdO thin films were grown by pulsed laser deposition. The ZnCdO thin films were wurtzite hexagonal structure with preferred growth along the (002) direction. All the samples were found to be highly transparent with an average transmission of about 80%similar to in the visible range. We have investigated the change of the performance of ZnCdO TFTs as the thickness of the active layer is increased. The carrier concentration of ZnCdO thin films has been confirmed to be increased from 10(16) to 10(19) cm(-3) as the film thickness increased from 30 to 100 nm. Base on this result, the ZnCdO TFTs show a thickness-dependent performance which is ascribed to the carrier concentration in the active layer. The ZnCdO UT with 30 nm active layer showed good off-current characteristic of below similar to 10(11), threshold voltage of 4.69 V, a subthreshold swing of 4.2 V/decade, mobility of 0.17 cm(2)/V s, and on-to-off current ratios of 3.37 x 10(4). (c) 2011 Elsevier B.V. All rights reserved.
Keywords: HIGH-MOBILITY